Analisis Ekonomi Usaha Ternak Kelinci - Darman, Darman (Bina Nusantara University, 2011)
Rabbit livestock development has been started since the 80s and received a positive response from all walks of society and government officials in addressing nutrition fulfillment. The main obstacle in its development is still a psychological effect among men with cattle and rabbits in terms of cutting as well as to eat. On the other animals are prolific rabbit and bear a short distance so as to produce a sufficiently high number of children in a short time unit (per year) so that the meat is known as a reliable provider. Rabbit farm business other than as a fulfillment of nutrition (subsistence) needs the support to lead to market-oriented commercial enterprises. Have tried to do an intensive analysis of enterprise-scale rabbit breeding 20 males and 5 tails as a business producing meat and pelts for one year. The results of the economic analysis suggests that gains on the scale of the business amounted to Rp 9.206.200/tahun or Rp 767.183/bulan (in this calculation is carried out an assessment of the remaining rabbit pieces that have not aged, as in cash opnam remainingÂ number of (young cattle).Â